Relationship between Systolic Arterial Pressure and Heart Mass in the Rat - Grassi de Gende, Ángela (1993)
This study describes the relationship between left ventricular mass and systolic arterial pressure (SAP) in normotensive and hypertensive rats. The genetically hypertensive rats (SHR) were stratified according to their SAP values in to hypertensive (SHRH) and normotensive (SHRN) subgroups. Males and females of both subgroups exhibited biventricular hypertrophy and the left ventricular mass was not correlated with SAP values. An overall cardiac enlargement was also found in female rats of the normotensive WKY group. In DOCA-salt and 2K/1C hypertensive rats the left ventricular mass was correlated positively with SAP. These data suggest that SAP is not a factor in the development of left ventricular hypertrophy in the SHR strain, however, they also revealed a right ventricular mass increase in this strain with respect to the Wistar strain.